Heparanase and cancer progression: New directions, new promises. Issue 9 (1st September 2016) - Arvatz, Gil; Weissmann, Marina; Ilan, Neta; Vlodavsky, Israel
ABSTRACT: Heparanase, the sole heparan sulfate degrading endoglycosidase, regulates multiple biological activities that enhance tumor growth, angiogenesis and metastasis. Much of the impact of heparanase on tumor progression is related to its function in mediating tumor-host crosstalk, priming the tumor microenvironment to better support tumor progression. Heparanase expression is enhanced in almost all cancers examined including various carcinomas, sarcomas and hematological malignancies. Numerous clinical association studies have consistently demonstrated that upregulated heparanase expression correlates with increased tumor size, tumor angiogenesis, enhanced metastasis and poor prognosis. Notably, heparanase is ranked among the most frequently recognized tumor antigens in patients with pancreatic, colorectal or breast cancer, favoring heparanase-based immunotherapy. Development of heparanase inhibitors focused on carbohydrate-based compounds of which 4 are being evaluated in clinical trials for various types of cancer, including myeloma, pancreatic carcinoma and hepatocellular carcinoma. Owing to their heparin-like nature, these compounds may exert off target effects. Newly generated heparanase neutralizing monoclonal antibodies profoundly attenuated myeloma and lymphoma tumor growth and dissemination in preclinical models, likely by targeting heparanase in the tumor microenvironment.